EDUKASI PEMANFAATAN LIMBAH HASIL PERIKANAN PADA KELOMPOK PKK DI NEGERI PASSO KECAMATAN BAGUALA, KOTA AMBON - Bernita br. Silaban; Johanna Tupan; Vonda MN Lalopua; Venia Vanessya Latekay; Rafenska Malaihollo; Tirsya Afriana Gai (Universitas Mataram, 2023)
The availability of fish in Passo State is quite adequate, but the community does not yet have good skills to process these marine products into products with high economic value. The caught fish is often sold whole or filleted. Waste in the form of bones, heads, fins, scales and entrails is usually thrown away, without being processed. In fact, if the waste can be managed properly it will produce derivative products that can be an alternative source of new income. This PKM activity aims to provide education to the public about how to properly and correctly handle and utilize fishery product waste and be able to process waste into products that have economic value. The method of implementing this activity includes lecture, discussion and training methods. Lectures are presented in the form of power point presentations followed by the training process. Partners who become suggestions are PKK mothers. Participants were given knowledge and technology on how to process fishery waste. Some of the training materials were delivered theoretically as additional knowledge of the community and some were delivered practically in the form of training on making various creations from fish scales. Participants were very enthusiastic about participating in this training activity because this activity was something new for them. Participants understand how to handle and utilize fishery waste and can practice making accessories from fish scales well. The results of the pre-test and post-test showed that the counseling and training provided to PKK mothers had a positive impact on the transfer of knowledge and technology (science and technology), especially regarding the handling and utilization of fishery waste.